KEBIJAKAN KERINGANAN DENDA DI KOPERASI SIMPAN PINJAM SEDANA WERDI BR. DANGIN TANGGLUK KESIMAN PADA MASA PANDEMI COVID 19 - Putu Siti Firmani (Jurnal Ilmiah Satyagraha, 2022)
The presence of Covid-19 brings global challenges to create a newsocial order or recovery. Financial institutions such as banks, cooperatives andLPDs on the island of Bali are also feeling the impact of the Covid-19 virus.Sedana Werdi Cooperative is one of the savings and loan cooperatives on theisland of Bali. The Sedana Werdi Cooperative implements several policies for itsmembers, one of which is the existence of fines for members who do not pay loansand interest on time. The approach used by the author is descriptive qualitative,namely a description based on the results of observations, interviews and validity,which is based on the process of issuing this fines relief policy, especially in theSedana Werdi Cooperative Br. Dangin Tangluk Kesiman. The data collection techniques in this study were observation, interviews, and documentation. Thetriangulation used is technique triangulation and source triangulation.Triangulation technique is done by collecting data from observations, interviews,and documentation. Source triangulation is done by collecting data throughinformation sources, namely through interviews with the head of the SedanaWerdi Savings and Loans Cooperative. The Sedana Werdi Cooperative is here toprovide solutions to its members affected by the recession. The Covid-19pandemic has had an impact on business and financial health. Based on theseconditions, the Sedana Werdi Cooperative offers its members an exemption fromthe obligation to pay the previously imposed fines.